2017
DOI: 10.1039/c7ta01976a
|View full text |Cite
|
Sign up to set email alerts
|

Facile solvothermal synthesis of Pt76Co24 nanomyriapods for efficient electrocatalysis

Abstract: Uniform Pt76Co24 myriapods with abundant active sites were prepared by a one-pot solvothermal method, which exhibited excellent catalytic performances for ORR and HER in acid media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…The four characteristic diffraction peaks show up at 40.8°, 47.4°, 69.4° and 82.9°, which correspond to the (111), (200), (220) and (311) crystal facets of the fcc PtCo alloy, respectively . Moreover, these diffraction peaks coincidently emerge between those of standard Co (JCPDS‐05‐0727) and Pt (JCPDS‐04‐0802), forcefully confirming the formation of the PtCo alloy …”
Section: Resultsmentioning
confidence: 59%
“…The four characteristic diffraction peaks show up at 40.8°, 47.4°, 69.4° and 82.9°, which correspond to the (111), (200), (220) and (311) crystal facets of the fcc PtCo alloy, respectively . Moreover, these diffraction peaks coincidently emerge between those of standard Co (JCPDS‐05‐0727) and Pt (JCPDS‐04‐0802), forcefully confirming the formation of the PtCo alloy …”
Section: Resultsmentioning
confidence: 59%
“…However, the large overpotential and sluggish ORR kinetics due to the multielectron transfer process requires an effective catalyst to facilitate the ORR. Platinum (Pt)‐based materials have been regarded as the most effective ORR catalysts, whereas extreme scarcity and high‐cost largely limit their practical applications . Substantial research efforts have been dedicated to substitute Pt by various strategies without compromising the electrocatalytic performance .…”
Section: Methodsmentioning
confidence: 99%
“…Arginine was chosen as a good structure‐directing agent because of its attractive guanidine group ( Scheme a), which has unique self‐assembly properties and coordination capacities (Scheme b), making it easy to build the highly alloying nanoassemblies via modulating both the nucleation and crystal‐growth kinetics. Despite biomolecules are commonly employed in building of Pt‐based nanocrystals with novel architectures, very few reports have looked into the Pd‐based nanocrystals with unique assemblies‐like structure. Furthermore, both Pd 3 Co and Pd 3 Ni nanoassemblies manifest the remarkably enhanced electrocatalytic properties in terms of activity and stability for the ORR relative to those of Pd nanoassemblies and Pd black catalysts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theb inding energy of Co 0 (Co 2p 3/2 :7 77.8 eV) was shifted to al ower energy compared to that reported in the literature (Co 2p 3/2 :778.3 eV), [12] which indicates the alloying of Co with Pd. [13] From the XPS data, the Pd 0 :Co 0 atomic ratio was found to be 7:3. We found that ca.…”
mentioning
confidence: 98%